2014
DOI: 10.3389/fimmu.2014.00605
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study on Health-Related Quality of Life in a Cohort of 96 Patients with Common Variable Immune Deficiencies

Abstract: Health-related quality of life (HRQoL) in common variable immunodeficiency diseases (CVID) was evaluated by different tools, which were mainly used to compare different schedules of immunoglobulins administration in cross-sectional or short-term longitudinal studies. We assessed the HRQoL and psychological status of CVID patients in a longitudinal study over a 6-year period by a generic, non-disease-specific instrument (SF-36), and by a General Health Questionnaire (GHQ-12) for the risk of depression/anxiety. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 23 publications
(27 reference statements)
7
51
0
Order By: Relevance
“…However, when fitted into a multivariate model their influence on fatigue became insignificant when paired with the other variables in the predicted model. Similarly, CVID patients with chronic GI and lung disease had lower QoL and higher mortality rate than did those free of such complications [8,16], and while permanent lung damage was not a significant variable in predicting fatigue in multivariate analysis, having permanent lung damage increased the odds of fatigue in a univariate analysis [OR = 1·46, P = 0·045, 95% confidence interval (CI) = 1·01-2·13]. However, previous studies showed that, in the general population, fatigue is reported more frequently by females than in males [10,15].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, when fitted into a multivariate model their influence on fatigue became insignificant when paired with the other variables in the predicted model. Similarly, CVID patients with chronic GI and lung disease had lower QoL and higher mortality rate than did those free of such complications [8,16], and while permanent lung damage was not a significant variable in predicting fatigue in multivariate analysis, having permanent lung damage increased the odds of fatigue in a univariate analysis [OR = 1·46, P = 0·045, 95% confidence interval (CI) = 1·01-2·13]. However, previous studies showed that, in the general population, fatigue is reported more frequently by females than in males [10,15].…”
Section: Discussionmentioning
confidence: 97%
“…We have also shown that patients who report fatigue have a significantly lower quality of life (QoL) than those in a normative sample of the general US population (P < 0·05) [7]. Poor QoL is an independent predictor of mortality in CVID [8], especially in patients with severe noninfectious complications [9]. Importantly, it has been projected that improving the QoL score by one point may reduce the risk of death by 2-3% [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of PID presents a challenge to pediatricians due to rare incidence and unspecific symptoms, resulting in delayed referral and negative outcome for patients and parents (3, 4). The pre-diagnostic experience of patients and their families is not sufficiently integrated into the diagnostic process.…”
Section: Discussionmentioning
confidence: 99%
“…Although progress in genetic definition has been made, clinical diagnostics remains a challenging task for the general practitioner (GP) or pediatrician. Early diagnosis is of paramount importance because the delay leads to increased mortality, morbidity, and reduced quality of life (3, 4). Although the time to diagnosis varies, diagnostic delay is common (58).…”
Section: Introductionmentioning
confidence: 99%